The Relationship of Mutations in the MTHFR, Prothrombin, and PAI-1 Genes to Plasma Levels of Homocysteine, Prothrombin, and PAI-1 in Children and Adults - Balasa, Vinod V.; Gruppo, Ralph A.; Glueck, Charles J.; Stroop, Davis; Becker, Ann; Pillow, Ann; Wang, Ping (Thrombosis and Haemostasis, 1999)
Studies in adults have demonstrated that the genetic mutations C677T methylenetetrahydrofolate reductase (MTHFR), prothrombin 20210A, and the 4G polymorphism of the plasminogen activator inhibitor-1 (PAI-1) gene are associated with elevated plasma levels of homocysteine, prothrombin and PAI-1, respectively and with an increased risk of thrombosis. No similar data is available in children. Therefore, we assessed the relationship of plasma levels of homocysteine, prothrombin and PAI-1 with their respective mutations in 197 normal children, compared to 40 adults. By stepwise multiple regression, homocysteine was positively associated with age, PAI-1 activity was negatively associated with age, while PAI-1 antigen and prothrombin levels were associated with gender, being higher in girls than boys. When the genotypes were added to the regression model as additional explanatory variables, the MTHFR genotype accounted for 2.9% of the variance of homocysteine (p = 0.024), and the PAI-1 gene accounted for 2.7% of the variance of PAI-1 antigen levels (p = 0.023). Of children homozygous for the MTHFR mutation, 35% had homocysteine levels ≥ the age-specific 95th percentile, compared to 2% hetero-zygotes and 5% wild type normals (p = 0.0001). The mean homocysteine level was higher in children homozygous for the MTHFR gene (8.4 μmol/l) than in heterozygotes (5.5 μmol/l), p <0.05. Of children homozygous for the 4G polymorphism of the PAI-1 gene, 19% had PAI-1 activity levels ≥ the age-specific 95th percentile, compared to 2% of heterozygotes and 3% of wild type normals (p = 0.003). Studies of the incidence of the MTHFR, prothrombin, and PAI-1 4G/5G genotypes in children with thrombosis, when compared to these healthy normals, will provide evidence as to which of these genes are associated with thrombophilia.This work was carried out following an institutional research committee approved protocol with signed informed consent.